Write to the point : a master class on the fundamentals of writing for any purpose - Leith, Sam (The Experiment, LLC, 2018)
Good writers follow the rules. Great writers know the rules -- and follow their instincts! Finding the right words, in the right order, matters -- whether you're a student embarking on an essay, a job applicant drafting your cover letter, an employee composing an email . . . even a (hopeful) lover writing a text. Do it wrong and you just might get an F, miss the interview, lose a client, or spoil your chance at a second date. Do it right, and the world is yours. In Write to the Point, accomplished author and literary critic Sam Leith kicks the age-old lists of dos and don'ts to the curb. Yes, he covers the nuts and bolts we need to be in complete command of the language: grammar, punctuation, parts of speech, and other subjects half-remembered from grade school. But more importantly, he charts a commonsense course between the "Armies of Correctness" and the "Descriptivist Irregulars." For Leith, knowing not just the rules but also how and when to ignore them -- developing an ear for what works best in context -- is everything. In this master class, Leith teaches us a skill of paramount importance in this smartphone age, when we all carry a keyboard in our pockets: to write clearly and persuasively for any purpose -- to write to the point. - Publisher.